The Use of 2 Dimensional Animation as A Medium For Early Chilhood Learning in Youtube Media - Gede Lingga Ananta Kusuma Putra; Gede Pasek Putra Adnyana Yasa; Gede Basuyoga Prabhawita (Journal of Art, Film, Television, Animation, Games and Technology, 2022)
Animation is an image or character that is created or created with the movement where the creation process uses computer media.  Due to technological developments that are now increasingly rapid, which has resulted in the existence of various types of animation, one of which is 2-dimensional animation, where 2-dimensional animation is a form of animator's work in making an image or creating a character and bringing it to life through a movement. Due to the many types of animation, the idea emerged which uses 2-dimensional animated videos as a learning medium so that learning becomes more fun and more effective. Animated videos are chosen as videos that can be used as learning media because these animated videos can attract the sympathy of children to learn and also attract their curiosity to increase because the plot or story in the animated video is made as fun as possible so that children feel at home or endure watching  video to the end. Because this requires a platform or website that is easy for everyone to access, one of the websites that can be used is YouTube, where YouTube is a website that is used to share videos that promote a service, educate, or entertain.  not only as a website to share a video but most people also use YouTube as a website to find information, news, as a site to help learning or other things.  Animated videos as learning media are now very easy to find on YouTube media, especially learning animation videos for preschool children where the videos are very easy to find, with various types or different types of characters.